Biochemical and cellularchanges in Oreochromis niloticus related to the water pollution of a degraded river - doi: 10.4025/actascibiolsci.v35i3.13207 - Cruz, Zilma Maria Almeida; Castro, Rodrigo Roque Lesqueves de; Canal, Adriana; Azevedo Júnior, Romildo Rocha; Silva, Ary Gomes da; Ramos, Alessandro (Acta Scientiarum. Biological Sciences, 2013)
The effects of polluted water at three sites in the Marinho River, Brazil, on Oreochromis niloticus (Nile tilápia) were investigated using histological, hematological and biochemical approaches. Fish exposed to the impacted water demonstrated that histological changes in gills were accompanied by nuclear and micronuclei abnormalities in cells. The activity of liver and plasma biomarkers (alkaline phosphatase (ALP), acid phosphatase (ACP), alanine aminotransferase (ALT), aspartate aminotransferase (AST) and liver glutathione S-transferase (GST)) showed an expressive change due to the. The results were also correlated with the highest levels of Cu+2, Zn+2 and Mn+2 in the water. The data of this study evidenced the importance of using a set of biomarkers to quantify pollution in lentic ecosystems. Additionally, histological analyses of gills and erythrocytes have proven to be an important instrument for signaling the impact of pollutants in rivers.